Making the Holy Roman Empire holy: Frederick Barbarossa, Saint Charlemagne and the sacrum imperium - Sulovsky, Vedran (Cambridge studies in medieval life and thought, 2024)
"This book analyses the so-called sacralisation of the Holy Roman Empire during the reign of Frederick Barbarossa in the twelfth century, when the Empire's most commonly known name became popular. Innovative and comprehensive, it will interest scholars of the Middle Ages, specifically those interested in art, political, and ideological history"-- Provided by publisher